Classification of leisure participation in women with chronic conditions: a measurement tool - Supalak Khemthong (2018)
A measurement tool has been developed to classify and quantify participation in different types of leisure for adults with chronic health conditions. This tool is needed to provide more understanding of the contribution to health outcomes of positive and negative engagement in leisure activities. This paper reports on the development of the Classification of Leisure Participation (CLP) Scale for women with chronic conditions. Sixty‐one leisure and social activity items were generated from previous studies. Using a postal survey, 102 participants were asked to indicate whether each item represented mostly physical, social, educational/creative, or passive leisure. Using cluster analysis and a cut‐off of 60% agreement, 16 physical items, 14 social items, 0 educational/creative items, and 8 passive items were identified. Strong face validity was based on the item generation existing from research of women with chronic conditions. Strong internal consistency reliability (Cronbach's Alpha = 0.74) was found for the overall scale. Construct validity (hypothesis testing procedure) found mild to moderate correlations between physical/social leisure and some subscales of the SF‐36 at p < 0.05. The CLP Scale provides a mechanism to further investigate the impact of leisure participation on physical and mental health in adults.